The Effectiveness of using Spreadsheet Learning Media to Increase Student Learning Outcomes at SMAN 1 Sumbawa Besar - Zulkarnaen, Jonny; Umar, Umar; Hartono, Roni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
A good learning process must begin with planning in advance. in the learning process it must be done as attractively as possible so that students are motivated and enthusiastic to learn, The transition from the conventional learning process to digital learning provides a significant change, while the purpose of the study is to determine the extent to which the implementation and effectiveness of using spreadsheet learning media in improving student learning outcomes and to find out how much increase in student learning outcomes after learning using spreadsheet learning media. The type of research used is a mixed method with an experimental approach. The data collection technique used is a survey technique, with interview instruments, questionnaires and documentation. from the significance of the table that is 0.05. So that the pretest and posttest value data are normally distributed. To determine the difference in the results of the pretest and posttest, it was continued with a paired sample T test using the SPSS version 22.0 program with a calculated significance value of 0.000 and to see the effectiveness of using spreadsheet learning media, a statistical test was carried out using the N Gain score test. The results of the study found that the use of spreadsheet learning media was effective in improving learning outcomes with a percent N-Gain score of 47% which was in the medium category (quite effective).